Recurrence of chilblain-like lesions in children during the second COVID-19 wave. A prospective study. - Colonna, C.; Vezzoli, P.; Monzani, N.A.; Zussino, M.; Robustelli, E.; Petaccia, A.; Sena, P.; Cavalli, R. (European Journal of Pediatric Dermatology, 2022)
In this prospective study, we followed for over a year pediatric patients who had chilblains after the onset of SARS-CoV-2 pandemic. From March 2020 to September 2021, 110 pediatric patients with chilblains (average age 11 years, range 5-18 years) were observed. From September 2020 to September 2021, during the second wave of Covid-19 pandemic, 35 (31.8%) children displayed new-onset chilblains, while 13 (11.8%) presented a relapse (T2) of the skin lesions previously detected during the first peak of the pandemic (T1). Both groups underwent the same examinations, namely RT-PCR on nasopharyngeal-swab, IgG serology for SARS-CoV-2, capillaroscopy and complete blood tests.